Is Internal Rotation Measurement of the Hip Useful for Ruling in Cam or Pincer Morphology in Asymptomatic Males? A Diagnostic Accuracy Study. Issue 10 (13th October 2022) - Hilfiker, Roger; Hunkeler, Marc; Limacher, Andreas; Leunig, Michael; Bonel, Harald; Egger, Matthias; Jüni, Peter; Reichenbach, Stephan
Abstract: Background: Cam and pincer morphologies are associated with limited internal rotation. However, the routine clinical examination for hip rotation has limited reliability. A more standardized method of measuring hip rotation might increase test-retest and interobserver reliability and might be useful as a screening test to detect different hip morphologies without the need for imaging. We developed an examination chair to standardize the measurement of internal hip rotation, which improved interobserver reliability. However, the diagnostic test accuracy for this test is unknown. Question/purpose: Is a standardized method of determining internal hip rotation using an examination chair useful in detecting cam and pincer morphology with MRI as a reference standard? Methods: A diagnostic test accuracy study was conducted in a sample of asymptomatic males. Using an examination chair with a standardized seated position, internal rotation was measured in 1080 men aged 18 to 21 years who had been conscripted for the Swiss army. The chair prevents compensatory movement by stabilizing the pelvis and the thighs with belts. The force to produce the internal rotation was standardized with a pulley system. Previous results showed that the measurements with the examination chair are similar to clinical assessment but with higher interobserver agreement. A random sample of 430 asymptomatic males was invited to undergo hip MRI. Of those, 244 White European males responded to the invitation and had a mean age of 20 ± 0.7 years and a mean internal rotation of the hip of 33° ± 8.5°. Using MRI as the reference standard, 69% (169 of 244) had a normal hip, 24% (59 of 244) a definite cam morphology (Grades 2 and 3), 3% (8 of 244) an increased acetabular depth, and 3% (8 of 244) a combination of both. One experienced radiologist graded cam morphology as follows: 0 = normal, 1 = mild, 2 = moderate, and 3 = severe. Pincer morphology was defined by increased acetabular depth (≤ 3 mm distance between the center of the femoral neck and the line connecting the anterior and posterior acetabular rims). The intraobserver agreement was substantial (weighted κ of 0.65). A receiver operating characteristic (ROC) curve was fitted, and sensitivity, specificity, and likelihood ratios were estimated for different internal rotation cutoffs. Results: For cam morphology, the area under the ROC curve was 0.75 (95% CI 0.67 to 0.82). Internal hip rotation of less than 20° yielded a positive likelihood ratio of 9.57 (sensitivity 0.13, specificity 0.99), and a value of 40° or more resulted in a negative likelihood ratio of 0.36 (sensitivity 0.93, specificity 0.20). The area under the curve for detecting the combination of cam and pincer morphologies was 0.87 (95% CI 0.74 to 1.0). A cutoff of 20° yielded a positive likelihood ratio of 9.03 (sensitivity 0.33, specificity 0.96). Conclusion: This examination chair showed moderate-to-good diagnostic value to rule in hip cam morphology in White European males. However, at the extremes of the 95% confidence intervals, diagnostic performance would be poor. Nonetheless, we believe this test can contribute to identifying cam morphologies, and we hope that future, larger studies—ideally in more diverse patient populations—will seek to validate this to arrive at more precise estimates of the diagnostic performance of this test. Level of Evidence: Level III, diagnostic study.